BISERICA ARMEANĂ DIN ROMÂNIA – LIBERTATE DE CONȘTIINȚĂ ȘI TOLERANȚĂ RELIGIOASĂ (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2025)
Armenian Church in Romania - Freedom of Conscience and Religious Tolerance.In 301, Armenia became the first Christian state in the world. After the year 451, the Armenian Church rejected the Chalcedon Synod and thus separated from the Orthodox Church. Armenia falling under Arab and Turkish rule, most of the population emigrated, the Armenians had a diaspora, for hundreds of years, without having an independent state. Armenians settled on the territory of Romania starting from the 11th-12th centuries. Here they found an atmosphere conducive to the practice of their traditional occupations under conditions of religious tolerance. In 1401, the ruler Alexander the Good consecrated the establishment of the Armenian Episcopate with residence in Suceava. The Armenians were welcomed and favored by the rulers Stephen the Great and Alexander Mavrocordat. Although there were rulers who persecuted them, the Armenians had flourishing colonies in many cities, building churches and monasteries. In Basarabia there was an Armenian bishopric for over 100 years, and in Gherla an Armenian-Catholic one. After 1918, the  Armenian cult was recognized by the Romanian State as part of the historical Churches in the country. In 1931, the Armenian Diocese was established, with its seat in Bucharest.